Exploring differences between adolescents and adults with perinatal depression-data from the expanding care for perinatal women with depression trial in Nigeria (2019)
Background: Depression is common among women in the perinatal period. Although pregnancy and motherhood among adolescents are global public health issues, little is known about how adolescents differ from adults in the occurrence and correlates of perinatal depression. Methods: Data were derived from a cluster randomized controlled trial of psychosocial interventions for perinatal depression in primary maternal care in Nigeria (the Expanding Care for Perinatal Women with Depression trial). Adolescents and adult participants recruited during pregnancy and followed up till 6-month postpartum were compared: proportions with depression [screening positive to depression on the Edinburgh Postnatal Depression Scale (score ≥ 12) and meeting the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, criteria using the short form of the Composite International Diagnostic Interview]; adjustment and attitude to pregnancy and motherhood (using the Maternal Adjustment and Maternal Attitudes scale); and parenting skills (measured on Infant–Toddler version of the Home Inventory for Measurement of the Environment). Infant and fetal growth were assessed by measures of weight and head circumference at birth and upper mid-upper arm circumference (MUAC) at 6 months. Results: Of 8,580 adults screened, 6.9% had major depression compared with 17.7% of 772 screened adolescents (p < 0.001). Adolescents had significantly poorer adjustment and attitudes to pregnancy, lower mean fetal gestational age at birth, and a smaller mean baby’s birth weight. At 6-month postpartum, there were no significant differences in the rates of remission from depression between adolescent and adult women (Edinburgh Postnatal Depression Scale score <6). Adolescent mothers continued to have poorer maternal attitudes and parenting skills indicated by significantly lower scores on the Infant–Toddler version of the Home Inventory for Measurement of the Environment responsivity and involvement subscales. Infants of adolescent mothers had a higher rate of undernutrition (defined as MUAC < 12.5 cm) compared with those of adult mothers: 14.8 and 6.3%, respectively (p = 0.008), with the mean MUAC remaining significantly lower for infants of adolescent mothers after adjusting for their lower birth weight (p = 0.04). Conclusion: Perinatal depression is more common and is associated with poorer maternal attitudes and parenting skills in adolescents compared with those in adults. Evidence from this exploratory study suggests that in improving outcomes in infants of adolescent mothers with perinatal depression, depression treatment may need to be supplemented with specific approaches to improve parenting skills.